Angiotensin II Destabilizes Coronary Plaques in Watanabe Heritable Hyperlipidemic Rabbits. Issue 5 (May 2016) - Li, Shen; Wang, Yan-Ning; Niimi, Manabu; Ning, Bo; Chen, Yajie; Kang, Dedong; Waqar, Ahmed Bilal; Wang, Ziyun; Yu, Qi; Liu, Enqi; Zhang, Jifeng; Shiomi, Masashi; et al.
Abstract : Objective—: Increased plasma concentrations of angiotensin II (Ang II) have been implicated in many cardiovascular diseases, such as atherosclerosis, aortic aneurysms, and myocardial infarction, in humans. However, it is not known whether high levels of plasma Ang II affect coronary plaque stability and subsequent myocardial infarction. This study was designed to examine whether elevated plasma Ang II can directly induce coronary events, such as acute coronary syndrome. Approach and Results—: To examine the above hypothesis, we infused Ang II (100 ng/min per kg [low group] and 200 ng/min per kg [high group]) or saline vehicle via osmotic minipumps into Watanabe heritable hyperlipidemic rabbits, a model of human familial hypercholesterolemia and atherosclerosis. Infusion of Ang II resulted in mortality rates of 50% and 92% in the low- and high-Ang II groups, respectively, whereas there were no deaths in the vehicle group. Pathological analysis revealed that Ang II–infused Watanabe heritable hyperlipidemic rabbits that died showed myocardial infarction. Furthermore, Ang II–infused Watanabe heritable hyperlipidemic rabbits exhibited coronary plaque erosion and rupture that were associated with thrombosis. Conclusions—: These findings suggest that increased blood levels of Ang II can destabilize coronary plaques and trigger the thrombosis, which possibly induces myocardial infarction. The model described in this study provides a novel means for the study of human acute coronary syndrome. Abstract : Supplemental Digital Content is available in the text.